2012
DOI: 10.1161/circheartfailure.112.970525
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Low Relative Lymphocyte Count in Patients Hospitalized for Heart Failure With Reduced Ejection Fraction

Abstract: Background-Low lymphocyte count has been shown to be an independent prognostic marker in heart failure (HF) in the outpatient setting. Limited data exist regarding whether relative lymphocyte count correlates with postdischarge outcomes in patients hospitalized for HF. Methods and Results-We performed a post hoc analysis of the Efficacy of Vasopressin Antagonism in Heart FailureOutcome Study with Tolvaptan (EVEREST) trial, which randomized 4133 patients hospitalized for worsening HF with an ejection fraction ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 35 publications
5
66
0
4
Order By: Relevance
“…Consistent with this, we also observed that prolonged QRS duration was associated with elevated NLR values, and diminished survival in our study. A post-hoc analysis of the Efficacy of Vasopressin Antagonism in Heart Failure Outcome Study with Tolvaptan (EVEREST) showed similar findings, where lymphopenia was associated with widened QRS duration and older age (both markers of worse prognosis) [24]. Prolonged QRS reflects more extensive myocardial damage, and the adverse ventricular remodeling that accompanies this (vide supra).…”
Section: Discussionmentioning
confidence: 83%
“…Consistent with this, we also observed that prolonged QRS duration was associated with elevated NLR values, and diminished survival in our study. A post-hoc analysis of the Efficacy of Vasopressin Antagonism in Heart Failure Outcome Study with Tolvaptan (EVEREST) showed similar findings, where lymphopenia was associated with widened QRS duration and older age (both markers of worse prognosis) [24]. Prolonged QRS reflects more extensive myocardial damage, and the adverse ventricular remodeling that accompanies this (vide supra).…”
Section: Discussionmentioning
confidence: 83%
“…31) Meanwhile, a low relative lymphocyte count has been independently associated with an increased mortality rate in patients with heart failure. 10,32) Thus, the N/L ratio, as an integrated reflection of two important immune pathways, is more potent and predictive than either parameter alone. Study limitations: This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to predicting long-term recurrent myocardial infarction (MI) in patients with ST-segment elevation MI, a low lymphocyte count may also predict the risk of reduced hemodynamics and aerobic capacity in patients with heart failure (7). A low lymphocyte count is also an independent predictor of poor outcomes for patients with heart failure during hospitalization (8).…”
Section: Introductionmentioning
confidence: 99%